Transition‐Metal‐Free Catalytic Hydrodefluorination of Polyfluoroarenes by Concerted Nucleophilic Aromatic Substitution with a Hydrosilicate. (22nd November 2017) - Kikushima, Kotaro; Grellier, Mary; Ohashi, Masato; Ogoshi, Sensuke
Abstract: A transition‐metal‐free catalytic hydrodefluorination (HDF) reaction of polyfluoroarenes is described. The reaction involves direct hydride transfer from a hydrosilicate as the key intermediate, which is generated from a hydrosilane and a fluoride salt. The eliminated fluoride regenerates the hydrosilicate to complete the catalytic cycle. Dispersion‐corrected DFT calculations indicated that the HDF reaction proceeds through a concerted nucleophilic aromatic substitution (CSN Ar) process.